139 Endothelial specific insulin resistance promotes the development of atherosclerosis. (9th June 2011) - Gage, M C; Yuldasheva, N; Jackson, C; Kearney, M; Imrie, H; Viswambharan, H; Kahn, M; Smith, J; Galloway, S; Cubbon, R; Sukumar, P; Aziz, A; et al.
Abstract : Background: Global insulin resistance and endothelial dysfunction have been identified as predisposing factors for atherosclerosis. However, it is unclear whether selective insulin resistance in endothelial cells alone, is sufficient to promote atherosclerosis. Here we addressed this question by crossing Endothelial Specific Mutant Insulin Receptor Over-expressing (ESMIRO) mice with ApoE null mice. ESMIRO mice over-express a human insulin receptor with Ala-Thr1134 mutation in the tyrosine kinase domain (which disrupts insulin signalling) selectively in endothelial cells under the control of the tie-2 promoter/enhancer. Methods: Male ApoE −/− ESMIRO mice were compared with sex-matched littermate ApoE −/− mice (both on a C57Bl6 background) after feeding a Western-style diet for 12 weeks. Results: ApoE −/− ESMIRO mice were morphologically indistinguishable from ApoE −/− control littermates, with normal development and no difference between groups in body mass. Heart rate, systolic blood pressure, glucose tolerance, insulin sensitivity and fasting glucose levels were similar in ApoE-/-ESMIRO and ApoE −/− mice. Aortic lipid deposition, assessed by en-face oil red O staining, was similar in ApoE −/− ESMIRO and ApoE −/− mice (6.4%±0.5% vs 5.8%±0.5%; p=0.39). However, atherosclerotic lesion area in cross sections of aortic sinus was significantly increased in ApoE −/− ESMIRO mice compared to ApoE −/− controls (24.8%±2.4% vs 16.6%±2.4%; p=0.02). Absolute plaque size was also significantly increased in ApoE −/− ESMIRO mice compared to ApoE controls (226 448.9±16 154 μm 2 vs 149 424.41±24 221 μm 2 ; p=0.01). Conclusions: Endothelial specific insulin resistance is sufficient to promote atherosclerosis and increase lesion area in ApoE null mice. This suggests that enhancing endothelial insulin sensitivity may be an appropriate target to prevent atherosclerosis in insulin-resistant conditions.